Prevalence and Trends of Adult Obesity in the US, 1999–2012. (19th December 2013) - An, Ruopeng
Abstract : Aim . To provide national estimates of obesity among US adults aged 20 years and older in 2011-2012 and track its trends from 1999 to 2012. Methods . Measured weight/height from National Health and Nutrition Examination Survey 1999–2012 waves was used to calculate body mass index (BMI) and prevalence measures. Piecewise logistic regressions were conducted to test the differential trends before and after 2010. Results . In 2011-2012, the age-adjusted prevalence of overweight and obesity combined ( BMI ≥ 25 ) was 71.1% (95% CI: 68.0%–74.2%) among men and 65.5% (61.8%–69.3%) among women, and the prevalence of obesity ( BMI ≥ 30 ) was 33.3% (30.5%–36.2%) among men and 35.8% (32.3%–39.4%) among women. From 1990–2000 to 2009-2010, the prevalence of overweight and obesity combined, obesity, grades 2 and 3 obesity combined ( BMI ≥ 35 ), and grade 3 obesity ( BMI ≥ 40 ) increased by 7.2%, 17.8%, 17.6%, and 33.0%, respectively. Compared to 2009-2010, most gender- and race/ethnicity-specific prevalence measures remained unchanged or slightly decreased in 2011-2012. No significant difference in trends among prevalence measures was found before and after 2010. Conclusions . Concurrent evidence on the leveling off of obesity in the US is thin. Given its high prevalence and profound socioeconomic consequences, close monitoring of the trend is warranted.